Outcomes of simultaneous vs. sequential pars plana vitrectomy and cataract surgery - Moraru, Andreea Dana (Exp Ther Med, 2020)
The coexistence of cataract and vitreoretinal diseases is common in clinical practice. The technological achievements of the last decade in both types of surgeries, allow simultaneous interventions on lens and retina. This retrospective study assessed the morphofunctional results obtained after performing simultaneous surgeries in a series of 87 patients presenting with both pathologies. The cases were retrospectively reviewed from their clinical records from 2017 to 2019. The patients were divided into two groups: group 1 comprising 41 cases underwent the combined procedure and group 2 comprising 46 patients underwent vitrectomy, followed by cataract surgery after 3-10 months. The functional and anatomical outcomes and the complications were assessed pre- and post-operatively. The statistical analysis was carried out by MaxStat software. The final best corrected visual acuity (BCVA), in group 1 was <0.1 in 4.88% of the cases, 0.1 to 0.3 in 17.07%, 0.3 to 0.5 in 51.22% and >0.5 in 26.83% eyes. In group 2, the final BCVA, after both surgeries were completed was <0.1 in 8.7% cases, 0.1 to 0.3 in 30.43%, 41.3% were 0.3 to 0.5 and 19.57% were >0.5. During the cataract surgery, the most common intraoperative complication was miosis, followed by posterior capsule rupture. Postoperative, 12.2% cases from group 1 developed an immediate inflammatory reaction in the anterior chamber, and 17.07% presented with posterior capsular opacification (PCO). Simultaneous surgery is safe and effective in obtaining a good morphological and functional result and offers the advantage of a clear eye media that allows a safer vitrectomy and thus a quicker rehabilitation of the patient. The analysis of the risks and benefits of each procedure should be taken into account and the cases selected individually for either simultaneous or sequential surgery in order to obtain the best outcomes.